Design and development of a four-wheel tractor stability alarm system for operator safety - Imam Hidayat; Salokhe, Vilas M.; Gee-Clough, D.; Ahmed, Kazi Mohiuddin; ADB Japan (Bangkok : Asian Institute of Technology, 1996)
A new stability alarm system to sense the stability of the tractor and to warn the operator when the instability reached, was designed and fabricated. The transducer of the system can sense the change of ground normal load on the tractor wheel. Using the alarm circuit, the alarm can give the warning at a certain level of ground slope which can be set by varying the voltage reference. The trend of the output curve of stability transducer follows the sine or cosine curve depend on the heading and tilting angle of the tractor and agrees with the change of ground normal load on the wheel as measured by the weighpad. This agreement proved that the stability transducer can be used as a sensor to sense the existence of ground normal load on the wheel, which measured the tractor condition either stable or not.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1996
Keywords: Tractors -- Equipment and supplies